Comparison of Some Agronomic Character and yield of Triticale (X Triticosecale Wittmack) lines at Halabja and Qlyasan Regions of Kurdistan/Iraq - Chnar Hama Noori Meerza (Faculty of Agriculture, Merdeka University Surabaya, Indonesia, 2022)
The main aim of this study was to determine the optimum line of triticale (X Triticosecale Wittmack) and best location for cultivating. The experimental design used in this study was randomized complete block design with two replications. In this study 29 lines of triticale were applied to assess some agronomic character (Plant Height (cm), No. of Days from Seeding to 50% Anthesis, No. of Days from Seeding to Physiological maturity, No. of Days from 50% Anthesis to Physiological maturity, No. of Fertile Tiller/Plant ), yield character (Grain Yield (t/ha), Biological Yield (t/ha) and Harvest Index). Plowing methods were used twice for the area of the study in each region. In Qlyasan region sowing started on 21 December and on 25 December in Halabja region. A total of 29 triticale lines developed from the hybridized winter triticale lines were used with a set name of 41ITYN and was taken from The International Maize and Wheat Improvement Center (CIMMYT). The 29 triticale lines consisted of (802, 803, 804, 805, 806, 807, 808, 809, 810, 811, 812, 813, 814, 815, 816, 817, 818, 819, 820, 821, 822, 823, 824, 825, 826, 827, 828, 829 and 830). The result illustrated that ) the maximum plant height, No. of Days from Seeding to 50% Anthess, No. of Days from Seeding to Physiological maturity, No. of Days from 50% Anthesis to Physiological maturity and No. of Fertile Tiller/Plant was observed in lines (804, 809, 830, 827 and 807). The highest agronomic character was observed under cultivation of triticale in the Halabja location. The maximum Grain Yield (t/ha), Biological Yield (t/ha) and Harvest Index was observed in lines (802, 828 and 827). Cultivation of the plant in Halabja region also gave the highest yield.